A foray into the territory of training in the arts of puppetry: teaching and learning (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
In this article the Romanian director Irina Niculescu talks about her theatrical experience, reflecting on the philosophies of professional training in the Theater of Animated Forms.Keywords: Philosophy. Professional qualification. Theater of Animated Forms.